(untitled) (Global Journal of Management and Business Research, 2023)
The purpose of the paper is to investigate the influence of fiscal and monetary policy on stock market development in Ghana. The study adopted quantitative approach. Dynamic OLS regression technique was used for running the formulated model as well as Toda-Yamamoto Granger no-causality approach for the causal relationships. The first hypothesis fiscal policy (inflation) revealed a positive and significant effect on stock market development. The second hypothesis also revealed a negative and significant relationship between interest rate and stock market development. Monetary policy rate revealed a positive and significant relationship with stock market development. Thirdly, the causal model analyzed found two bi-directional relationships: between interest rate and monetary policy rate; and inflation and government revenue. The study recommends incorporate of both fiscal and monetary policies in a single model as their interaction exerts significant effect on the stock market development. Also, the study recommends moderate inflation which would propel the stock market to expand as the share prices increases.